Analysis of Dissolved and Colloidal Substance Degradation in Old Corrugated Container White Water by Fenton Method - Meng, G.Q.; Li, X.; Hu, L.Y.; Luo, L.X. (Asian Journal of Chemistry, 2015)
In order to degrade the dissolved and colloidal substance (DCS) in white water system of waste paper, Fenton method, as an advanced oxidation processes, was employed in treating old corrugated container (OCC) recycling white water to reduce negative effect on paper properties and running performance of the paper machine. In this study, the optimum conditions were determined as pH was 4, [H2O2] = 1 mol/L, [H2O2]/[FeSO4·7H2O] = 1.75 for the Fenton process. Under these conditions, the removal rate of CODCr and dissolved and colloidal substance is reaching to 75.41 and 46.72 %, respectively. The stability of dissolved and colloidal substance to metal ion by Fenton treated in wastepaper white water is significantly improved.